A new "on–off–on" g-C3N4 nanosheets fluorescent sensor for 5-Br-PADAP and Co2+ under acidic conditions. (6th January 2022) - He, Wen; Xie, Yongbo; Yin, Qiang; Zhao, Zixuan; Shi, Lang; Wang, Hongqing
Abstract : A novel "on–off–on" g-C3 N4 nanosheet fluorescent sensor based on IFE could detect 5-Br-PADAP and Co 2+ under acidic conditions. Abstract : Scientists are still working on developing a "turn-on" fluorescence sensor for Co 2+, especially in acidic solutions. A novel "on–off–on" fluorescence sensor based on g-C3 N4 nanosheets was designed and prepared in this paper. It was able to detect (2-(5-bromo-2-pyridylazo)-5(diethylamino)phenol (abbreviated to 5-Br-PADAP) and Co 2+ quantitatively by quenching and restoring the fluorescence of the g-C3 N4 nanosheet system, respectively. Also discussed are the effects of solvent, pH, order of addition, and interaction time of 5-Br-PADAP and Co 2+, as well as the concentration range of the object on measurement. Furthermore, in acidic conditions, the sensor demonstrated good selectivity and sensitivity. In the solvent system EtOH : H2 O (v/v = 1 : 9, pH = 3), the fluorescence intensity had a good linear relationship with 5-Br-PADAP and Co 2+ concentrations in the ranges of 0–15 μM and 0–10 μM, with low detection limits of 64 nM and 44 nM, respectively. Experiments and theoretical calculations were used to describe the interaction characteristics and sensing mechanism. It was eventually successful in detecting Co 2+ in environmental samples.